2022
DOI: 10.3389/fsurg.2022.807940
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Pancreaticoduodenectomy in Elderly Patients: Systematic Review and Meta-Analysis

Abstract: BackgroundThe safety and efficacy of laparoscopic pancreaticoduodenectomy (LPD) in elderly patients who often suffer from pre-existing conditions (e.g., cardiovascular diseases) and poor functional reserve remain unclear. This meta-analysis aimed to evaluate the safety and efficacy of LPD in elderly patients.MethodsA systematic literature search was conducted using the PubMed, Embase, Web of Science, and Cochrane Library databases. All studies published from their inception to January 2022 reporting perioperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
7
4
1
Order By: Relevance
“…The most important finding of our study was the significant lower relative risk for 90-day mortality rate in elderly patients that benefited from laparoscopic approach compared to classical surgery (RR = 0.56; 95%CI: 0.32-0.96; p = 0.037). Our results are different from those reported in all aged categories [17] and in the meta-analyses conducted by Wang et al [40] and by Zhang et al [41] focusing on elderly patients, that report similar odds ratio for 90-day mortality rate between OPD and LPD. These differences might be partially explained by different measurement tools and included studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The most important finding of our study was the significant lower relative risk for 90-day mortality rate in elderly patients that benefited from laparoscopic approach compared to classical surgery (RR = 0.56; 95%CI: 0.32-0.96; p = 0.037). Our results are different from those reported in all aged categories [17] and in the meta-analyses conducted by Wang et al [40] and by Zhang et al [41] focusing on elderly patients, that report similar odds ratio for 90-day mortality rate between OPD and LPD. These differences might be partially explained by different measurement tools and included studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The potential inter-study heterogeneity of our analysis for 90-day mortality was 0%, similar to that reported by Wang et al [40] at 1%; however, Zhang et al [41] reported higher heterogeneity among included studies, which was at 42%. The meta-analysis conducted by Wang et al [40] included one small size study with octogenarians [43], without any death recorded.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations